Boric acid effect in phenolic composites on tribological properties in brake linings - Mutlu, I.; Oner, C.; Findik, F. (Elsevier Sci Ltd, 2007)
In the present work, using a pad-on-disc-type wear tester, the tribological properties of the pad next to the disk made of cast iron were investigated with changing the substance of the components. As well, micro-structural characterisation of braking pads was performed using scanning electron microscopy and also temperature outcome of the pads was examined at the temperatures of 50-400 degrees C in the pressure of 1050 and 3000 kPa. Finally, the effect of environment to the pads was studied in water, salty water, oil and braking liquid media. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: brake friction materials; brake lining; phenolic composites; boric acid; friction; wear